Enhancing the oral reading fluency of grade 2 pupils through a home reading program - Quinopez, Glorificacion L.
"The study described the oral reading fluency of Grade 2 pupils in the public elementary school. The overarching goal of the study was to find out the difference of the oral reading fluency of Grade 2 pupils in terms of rate, accuracy and reading expression before and after their exposure to a parent-facilitated home reading program. To elucidate this difference, a one group pre-test-post-test design was used. Pre-test-post-test scores comparison was used to ascertain differences, if any; while qualitative analysis and comparison of oral reading fluency before and after the home reading program was guided by the automaticity, verbal efficiency and sociocultural theories. Findings revealed that the oral reading fluency of the Grade 2 pupils before their exposure to the home reading program was below their grade level benchmark. As such, reading rate was described as slow, effortful, inefficient and conscious. Word recognition skills were undeveloped. Miscues consisted of errors in mispronunciation, omission and substitution. Reading expression was inappropriate and unnatural. Results further showed that after exposure to the parent-facilitated home reading program, the oral reading fluency of the pupils substantially increased in score, with quantitative and qualitative improvements in terms of rate, accuracy and reading expression. Reading rate had the highest score increment. Most of the pupils read with automaticity, while the struggling readersread with improved rate. Reading accuracy has likewise improved significantly. The high score increment was due to the decreased mispronunciation, omission and substitution miscues.Reading expression has the least score increment and the least enhanced among the three oral reading elements. The pupils’ reading expression was basically either monotone or with inappropriate rising and falling of tone in most part of the reading. The Home Reading Program, through the distinct form of scaffolding from family members, is an appropriate and effective intervention to help the beginning readers’ transition from word-by-word reading to fluent reading habit. The Home Reading Program in this study was based on the developmental perspective, automaticity and verbal efficiency perspectives which claim that oral reading fluency must be addressed at the beginning of the reading acquisition process, not after reading is already acquired. It is recommended that further investigation should be done on the correlation between oral reading fluency and comprehension enhancement in order to extensively establish research-based practices that will address the oral reading fluency development of the beginning readers in the context of English as second language. Family literacy programs that focus on oral reading fluency should be introduced and strengthened in parent-teacher associations and in community-based literacy programs. Future research on the current study should focus on a sample of students from diverse backgrounds to make the findings more conclusive and generalizable to the general population. Also, the use of an experimental design-randomized pre-test-post-testcontrol group design is recommended for future researches on oral reading fluency." --